Developmental Evaluation of the CHOICE+ Champion Training Program - Sarah A. Wu; Heather H. Keller; Rachael Donnelly; Emily Lambe; Hilary Dunn-Ridgeway (Journal of Long-Term Care, 2021)
Context: Mealtimes in residential care homes are important for social engagement and can encourage resident relationships. Yet, training programs to improve mealtime care practices in residential care settings remain limited in learning approaches and scope.